ANALISIS IMPLEMENTASI KEBIJAKAN PENCEGAHAN DAN PENANGGULANGAN HIV/AIDS DI PUSKESMAS HELVETIA KOTA MEDAN - Muchti Yuda Pratama; Fitriani Pramita Gurning (Indonesian Trust Health Journal, 2020)
HIV/AIDS is a disease that continues to grow and become a global problem that swept the world. According to WHO (World Health Organization) data in 2017, the discovery of cases of HIV (Human Immunodeficiency Virus) in the world reached 36.9 million people living with HIV, estimated at 0.8% of people aged 15-49 years worldwide living with HIV. The purpose of this study was to determine the implementation of HIV/AIDS prevention and control policies in Helvetia Health Center, Medan. This research uses descriptive qualitative research. The informants chosen in the in-depth interview are the holders of HIV/AIDS prevention and control policy programs at the Helvetia Health Center. The number of respondents who filled out the questionnaire was 30 randomly drawn. Triangulation was carried out to check the validity of the data obtained from the results of interviews with informants and the results of filling out the questionnaire by the community in the Helvetia Puskesmas work area. Based on the results of research and discussion on the implementation of HIV/AIDS prevention and control policies conducted by the Helvetia Health Center using the theory of George C. Edward III, it is known that the communication between the implementers of the HIV / AIDS policy program at Helvetia Health Center with the target groups has been going well, the resources the HIV / AIDS program at Helvetia Health Center as a whole is good enough, the disposition or attitude of implementing tendencies already looks very good and the bureaucratic structure factor that can be seen from the indicators is also known that it has been going well. Abstrak Penyakit HIV/AIDS merupakan suatu penyakit yang terus berkembang dan menjadi masalah global yang melandadunia. Menurut data WHO (World Health Organization) tahun 2017, penemuan kasus HIV (Human Immunodeficiency Virus) di dunia mencapai 36,9 juta orang hidup dengan HIV, diperkirakan sebanyak 0,8% orang berusia 15-49 tahun di seluruh dunia hidup dengan HIV. Tujuan penelitian ini untuk mengetahui pengimplementasian kebijakan pencegahan dan penanggulangan HIV/AIDS di Puskesmas Helvetia Medan. Penelitian ini menggunakan jenis penelitian kualitatif yang bersifat deskriptif. Informan yang dipilih dalam wawancara mendalaman adalah pemegang program kebijakan pencegahan dan pengendalian HIV/AIDS di Puskesmas Helvetia. Jumlah responden yang mengisi kuesioner sebanyak 30 yang diambil secara acak. Triangulasi dilakukan untuk memeriksa keabsahan data yang diperoleh dari hasil wawancara terhadap informan dan hasil pengisian kuesioner oleh masyarakat diwilayah kerja Puskesmas Helvetia. Berdasarkan hasil penelitian dan pembahasan mengenai implementasi kebijakan pencegahan dan pengendalian HIV/AIDS yang dilakukan oleh Puskemas Helvetia yang menggunakan teori George C. Edward III, diketahui bahwa komunikas iantara pelaksana program kebijakan HIV/AIDS di Puskesmas Helvetia dengan kelompok sasaran telah berjalan dengan baik, sumberdaya pada program HIV/AIDS di Puskesmas Helvetia secara keseluruhan sudah cukup baik, disposisi atau sikap kecenderungan pelaksana sudah terlihat sangat baik dan pada faktor struktur birokrasi yang dapat dilihat dari indikator-indikator juga diketahui bahwasannya telah berjalan dengan baik.